2022
DOI: 10.1177/09636625221093897
|View full text |Cite
|
Sign up to set email alerts
|

The legitimacy of science and the populist backlash: Cross-national and longitudinal trends and determinants of attitudes toward science

Abstract: Public attitudes toward science have risen for decades yet dropped in the most recent period coinciding with the emergence of anti-scientific populist discourses around the world. Controlling for a number of attitudinal and demographic factors, this study examines whether populist discourse and vote share as well as regime polity have an impact on the public legitimacy of science in the period 2005–2020. Cross-national findings suggest that populism is a consistent predictor of declining support for science ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Although we do not interpret the relatively low reference to traditional academic science organizations as an outcome of damaged authority of science, we see it as a condition, which may facilitate the rise of contestations of traditional scientific authorities in parliamentary political discourse. Social scientists have paid increasing attention to the rise of anti-scientific populist discourse-often termed as post-truth politics-in other contexts (particularly in mediatized political discussion) and in many countries around the world (Norris & Inglehart, 2019;Zapp, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we do not interpret the relatively low reference to traditional academic science organizations as an outcome of damaged authority of science, we see it as a condition, which may facilitate the rise of contestations of traditional scientific authorities in parliamentary political discourse. Social scientists have paid increasing attention to the rise of anti-scientific populist discourse-often termed as post-truth politics-in other contexts (particularly in mediatized political discussion) and in many countries around the world (Norris & Inglehart, 2019;Zapp, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Although we do not interpret the relatively low reference to traditional academic science organizations as an outcome of damaged authority of science, we see it as a condition, which may facilitate the rise of contestations of traditional scientific authorities in parliamentary political discourse. Social scientists have paid increasing attention to the rise of anti‐scientific populist discourse—often termed as post‐truth politics—in other contexts (particularly in mediatized political discussion) and in many countries around the world (Norris & Inglehart, 2019; Zapp, 2022). The existing literature on the topic has indicated that populist movements indeed frequently contest specific science‐based policy agendas (recently most notably related to climate change and vaccinations), produce general suspicion on science, and thus challenge the authority of traditional scientific institutions (McIntyre, 2018; Mede & Schäfer, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Populists undermine trust by embracing a rhetorical style that challenges the legitimacy of government (Norris and Inglehart 2019), and they circumvent political institutions as a strategy to claim a direct line to “the people” as their sole authentic voice. Some research finds that populism generates a general distrust towards institutions of power, including science or scientists (see Rosenfeld 2020; Zapp 2022). In this regard, populism is closely related to both a general critique of expertise (Davies 2019; Norris and Inglehart 2019) and a resurgent anti-intellectualism, a negative affect towards elites or an “intellectual establishment” that supposedly suffers from liberal bias (Barker et al 2022; Citrin and Stoker 2018).…”
Section: Literature Review: Mistrust and Its Epistemic Effectsmentioning
confidence: 99%
“…While there are tremendous benefits to a more egalitarian scientific ecosystem, there are also great societal risks if scientific literacy is not prioritized as a personal, cultural, economic, or democratic imperative ( 1 , 2 ). Antiscientific attitudes and the spread of scientific misinformation have become increasingly more common over the past several years, posing a grave risk to public health, political stability, and environmental sustainability ( 3 5 ). Scientific literacy can counteract or serve as an immunization against misinformation and antiscientific rhetoric ( 6 8 ).…”
Section: Introductionmentioning
confidence: 99%